Dilated cardiomyopathy in a green-winged saltator (Saltator similis) - Duarte, José Lucas Costa; Santos Junior, Wellington Martins dos; Oliveira Filho, Hodias Sousa de; Paranhos, Gabriel Forte; Pereira, Helder Carlos Costa; Araújo, Jeann Leal de (Brazilian Journal of Veterinary Pathology, 2024)
Cardiovascular diseases are rarely reported in birds. Among pet birds, they are most documented in psittacine birds. Dilated cardiomyopathy is a myocardial disease frequently found in poultry but with few reports in both pet and wild birds. An elderly male green-winged saltator (Saltator similis) died suddenly after presenting intermittent clinical signs of dyspnea, weakness, and vocalization changes. A general increase in cardiac size with a bulging apex was observed at necropsy. The heart exhibited an enlarged left ventricular space and flaccid musculature on the cut section. The liver was diffusely enlarged with rounded edges. No other gross lesions were observed. Samples were collected in 10% formalin and routinely processed. Histologically, bundles of myocardial fibers were irregularly arranged, with markedly elongated myofibrils and irregular cell contours. Additionally, multifocal areas of disruption were observed between the myofibrils. Diffuse hepatic congestion of sinusoids and portal veins was observed, and diffuse edema in the interstitium and para bronchi was present in the lungs. The clinical signs observed were nonspecific and can be found in several diseases of the cardiovascular and respiratory systems of birds. The gross and histological findings are compatible with what has been described for dilated cardiomyopathy in birds; however, left ventricular dilatation is uncommon in avian patients. Heart diseases in pet birds are still underdiagnosed, and reports of cardiomyopathies are limited to psittacine birds. To the authors’ knowledge, this is the first report of a dilated cardiomyopathy in a passerine bird.